Gang Members, Gang Affiliates, and Violent Men: Perpetration of Social Harms, Violence-Related Beliefs, Victim Types, and Locations - Wood, Jane L. (Journal of interpersonal violence, 2022)
Adult gang involvement attracts little empirical attention, so little is known about how they compare to nongang violent men in social harms beyond gang contexts. This study, based on unpublished data of 1,539 adult males, aged 19 to 34, from the Coid et al. national survey, compared gang members? (embedded in a gang; n?=?108), affiliates? (less embedded in a gang; n?=?119), and violent men?s (no gang association; n?=?1,312) perpetration of social harms by assessing their violence-related dispositions and beliefs, victim types, and locations of violence. Results showed that compared with violent men, gang members and affiliates were equally more likely to: cause social harms to a wider range of victims, including family and friends; seek violence; be excited by violence; and carry weapons. Gang members and affiliates were equally more likely than violent men to be violent at home, in friends? homes, and at work; they also thought about hurting people, but felt regret for some of their violence. A decreasing gradient was identified in gang members? (highest), affiliates? (next highest) and violent men?s (lowest) beliefs in violent retaliation when disrespected, the use of violence instrumentally and when angry, and worry about being violently victimized. Implications of findings are that interventions need to address anger issues across all levels of adult gang membership. Importantly, adult gang members? regrets regarding violence and anxiety about being violently victimized could be key factors that interventions could use to help them relinquish their gang involvement.